Visualising the design of conditions for urban social sustainability - Deirdre Greaney (Ambiances)
With increasing attention in urban design theory paid to conditions conducive to sustainable forms of urban experience, there is emerging emphasis on the non-technical perspective of sustainable urban design. This perspective focuses on design for urban social sustainability. Despite increasing exploration in this area, much of the theoretical conditions remain as text-based descriptions that lack graphic representation. This is due, in part, to contributions from disciplines traditionally not associated with visualisation. In considering the suggestive potential of this perspective for designers, this research seeks to ascertain if it can be represented visually. This article illustrates the beginning of a wider exploration into how to make visual the design of conditions for urban social sustainability. Testing how the non-technical perspective of sustainable urban design could be applied and communicated, this article highlights not only the value of the perspective but also the role of imaging in narrowing the gaps between urban design theory and practice and in the development of performative forms of imaging in the revelation of performative urban conditions.